Comparison of Resting Metabolic Rates: Calculated using predictive equation and measured using Portable Indirect Calorimeter - Yue Deng; Barbara J Scott (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2019)
Objective: The aim of this research was to examine differences between measured RMR from a portable indirect calorimetry device and calculated RMR from the predictive equation.  Methods: Seventy-nine participants were recruited for the study. RMR measures with the portable IC device were compared with RMR values calculated using Mifflin-St. Jeor Equation (MSJE). Subjects were divided base on body fat %: Group A included 35 lean/normal participants; Group B included 44 overweight participants. Results: Group A (r2=0.947): The mean RMR by IC was 49 kcal/day higher than MSJE (p=0.44). Considering a cut-off difference (calculated RMR-measured RMR) of ±200kcal/day, the RMR by IC was lower than MSJE for 28% of subjects and higher for 43%. Differences ranged from -890 to +670 kcal/day. Group B (r2=0.943): The mean RMR by IC was 147 kcal/day lower than MSJE (p=0.02). Considering a cut-off difference of ±200kcal/day, RMR by IC was lower than MSJE for 39% of subjects and higher for 20.5%. Differences ranged from -660 to +950 kcal/day. Conclusion: The analyses indicated no significant differences between the calculated and measured RMR for the groups. However, the individual RMR results support the use of the mobile IC to provide more accurate and personalized measurements of RMR.